#2**+5 **

6x-8y=-64 (1)

5x-8y=-60 (2)

Subtract equation 2 from 1 .... so we have....

x = -4 and substituting this into the first equation to find y, we have

6(-4) - 8y = - 64

-24 - 8y = -64 add 24 to both sides

-8y = - 40 divide both sides by -8

y = -40/-8 = 5

So....the solution is (x,y) = (-4, 5)

CPhill
Apr 21, 2015

#2**+5 **

Best Answer

6x-8y=-64 (1)

5x-8y=-60 (2)

Subtract equation 2 from 1 .... so we have....

x = -4 and substituting this into the first equation to find y, we have

6(-4) - 8y = - 64

-24 - 8y = -64 add 24 to both sides

-8y = - 40 divide both sides by -8

y = -40/-8 = 5

So....the solution is (x,y) = (-4, 5)

CPhill
Apr 21, 2015